Interlibrary loan practices handbook - Janke, Karen L.; Weible, Cherie L. (American Library Association, 2011)
In this new edition of the definitive Interlibrary Loan Practices Handbook, edited by CheriT Weible and Karen Janke, expert contributors clearly explain the complexities of getting materials for patrons from outside the library. This collection presents a complete view of the interlibrary loan (ILL) process, with contributions from all areas of the technical services community, providing